(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2019)
The lack of information about the effects of salinity on growth and productivity of triticale prompted us to study the salt tolerance level of 39 triticale lines and barley cultivar subjected to four levels of NaCl: control, 100, 150, 200 mM/L at stem elongation and maturity stages. This study was carried out in greenhouse at ICARDA during 2007, using Randomized Complete design with a factorial arrangement of treatments. Results revealed that the measured characters were affected by NaCl, with an interaction between treatments and lines. The influence of NaCl was observed at the levels 150 and 200 Mm/L more than the 100 Mm/L. Shoot dry weight was affected by salinity more than the root one. NaCl affected the biomass per plant and thousand kernels weight more than plant height, peduncle and spike length. At the two harvesting dates the lines: (14, 32, 13, 30, 34, 16, 10, 26, 19, and 22) characterized by the lowest reduction percentages in almost of measured traits. إن قلة المعلومات حول تأثير الملوحة في نمو وإنتاجية التريتيكالي عززت أهمية هذه البحث الذي تناول دراسة تحمل 39 سلالة من التريتيكالي وصنف من الشعير لأربعة مستويات من ملح كلور الصوديوم: 0، 100، 150، 200 ميلليمول/ليتر، وذلك خلال مرحلتي تطاول الساق والنضج. أجريت هذه الدراسة في بيت بلاستيكي في المركز الدولي للبحوث الزراعية في المناطق الجافة (إيكاردا) خلال العام 2007، باستخدام تصميم العشوائية الكاملة وفق ترتيب التجارب العاملية للمعاملات المدروسة. أظهرت النتائج أن الصفات المدروسة تأثرت بملح كلور الصوديوم مع وجود فعل متبادل بين المعاملات الملحية والسلالات. لوحظ تأثير الملح في المستويات المرتفعة 150 و200 ميلليمول/ليتر أكثر من المستوى 100 ميلليمول/ليتر. تأثر الوزن الجاف للمجموع الخضري بالملوحة أكثر من الوزن الجاف للجذور. كذلك فإن الكتلة البيولوجية للنبات ووزن الألف حبة قد تأثرتا بشكل أكبر من صفات ارتفاع النبات، وطول حامل السنبلة وطول السنبلة. لوحظ في كل من مرحلتي الدراسة أن السلالات (14، 32، 13، 30، 34، 16، 10، 26، 19، 22) أكثر تحملاً للملوحة مقارنةً بالسلالات الأخرى وصنف الشعير.